VStroll: An Audio-based Virtual Exploration to Encourage Walking among People with Vision Impairments - India, Gesu; Jain, Mohit; Karya, Pallav; Diwakar, Nirmalendu; Manohar, Swami (ASSETS (International ACM SIGACCESS Conference on Computers and Accessibility), 2021)
Current infrastructure design, discouragement by parents, and lack of internal motivation act as barriers for people with visual impairments (PVIs) to perform physical activities at par with sighted individuals. This has triggered accessible exercise technologies to be an emerging area of research. However, most current solutions have either safety concerns and/or are expensive, hence limiting their mass adoption. In our work, we propose VStroll, a smartphone app to promote walking among PVIs, by enabling them to virtually explore real-world locations, while physically walking in the safety and comfort of their homes. Walking is a cheap, accessible, and a common physical activity for people with blindness. VStroll has several added features, such as places-of-interest (POI) announcement using spatial audio and voice input for route selection at every intersection, which helps the user to gain spatial awareness while walking. To understand the usability of VStroll, 16 participants used our app for five days, followed by a semi-structured interview. Overall, our participants took 253 trips, walked for 50.8 hours covering 121.6 kms. We uncovered novel insights, such as discovering new POIs and fitness-related updates acted as key motivators, route selection boosted their confidence in navigation, and spatial audio resulted in an immersive experience. We conclude the paper with key lessons learned to promote accessible exercise technologies.